A system design study on AMH Philippines, Inc. - Bulos, Ian; Hernandez, Christina; Olandria, Elaine Bernadette
This paper is a comprehensive study on the total finance system of AMH Philippines, Inc. AMH is an engineering company located within the Bahay ng Alumni, UP Diliman. It was established in 1999, and has now over 100 employees. The company aims to provide clients with the best engineering solutions, nurture highly-technical and values-oriented employees, and create opportunities to partner with the academe and support the academe in instruction, research, and extension work. This study aims to analyze the company's current system and improve its processes through the application of system design concepts and tools. This study will focus on analyzing the current system of the finance department given the size of the company and the time constraint allotted for conducting the study and implementing the solutions. Interviews were conducted to understand the processes involved in the finance system, and to determine the pain points experienced by the finance team. Important documents involving the finance processes and relevant data were also collected. These were used in the creation of the steam diagnostic chart and pareto charts which were used to analyze the problem. From the logs it was determined that the lead time for the financial statement preparation took roughly 11 days, which was more than the ideal lead time set by the president. It was also determined from the logs that the finance team had consistent overtime with a range of 17-29% overtime per month. From the pareto charts, it was also determined that one of the tasks that took up most of the time was the encoding of the needed data. From the interview with the financial supervisor, it was also mentioned that the Management Information System (MIS) had limited functionality. Lastly, it was also mentioned that one of the reasons for the delay was the availability of the payroll which was only available for the finance team after every 4th of the month. From these, the proponents of the study were able to come up with the following alternatives. First alternative was the automation of the process for the scheduling of accounts. Since developing an information system takes up a lot of time, and given the time constraints, the proponents of the study were only able to come up with a proposed data flow diagram from the information system. This data flow diagram will be used by the company's MIS team to add a module for the scheduling of accounts to their already existing information system. The next alternative was the scheduling of certain tasks and processes. In ordet to meet the deadline for the Board of Director's meeting conducted on the nearest Monday to the 15th of each month, it was suggested that the financial statement preparation begin on the last Monday of the preceding month instead of the start of each month. In order to achieve this, the schedule of some tasks must be moved to earlier dates. The payout which happens on the 4th and 20th of the month will be moved to the 10th and 25th instead to ensure that payroll entries are made available earlier for the finance team. In the current system, there is no fixed day for the end of the billing invoice. In the proposed system, the Billing Letters must be received on the 2nd to last Friday of the month prior so that the Accounts Receivable entries would be available sooner. Lastly, it is proposed that the Request for Payments be received on the 2nd to the last Friday so that the approval and encoding process would be conducted on the last week of the month. The last alternative consists of transferring some of the tasks done by the Financial Supervisor to the other members of the finance team. Load charts were created to illustrate the current load of each finance team employee. Tasks from Quipse's (Financial Supervisor) load chart that were also present in the other employees' load chart were transferred to the said employee. For example, "PCF" which was being done by Quipse was also present in Bayot's load chart. Thus, in the new system, Bayot will completely take over PCF from Quipse so that Quipse would have more time for other financial statement tasks. Only tasks that were already being done by the other employees were transferred. This is to avoid having the other employees learn new tasks since the tasks being transferred are already familiar to them. Due to time constraints, the proponents of this study were not able to implement nor simulate the effect of the first alternative. After applying the proposed solutions for the 2nd and 3rd alternative in the simulation, the results show it is possible to shift the start date of the FS preparation by re-scheduling and re-assigning some of the tasks performed by the Financial Supervisor, without impacting total hours worked per week and per month. Therefore, by shifting the start date of the Financial Statement Preparation, it is safe to conclude that the Financial Statements will be available at the end of the 1st week of the month. This gives the Board of Directors 5 working days to review the Financial Statements prior to their Board Meeting on the 2nd Monday of the Month. The system performance can further be improved by implementing the other proposed alternative of automating the manual accounting processes.